2007
DOI: 10.1038/sj.ki.5002130
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure: Clinical implications based on the pathophysiology of its variability

Abstract: The circadian blood pressure (BP) rhythm is associated with worsened cardiovascular outcomes in patients who have an excessive morning BP surge and in those who lack the normal nocturnal BP fall (non-dippers). There are multiple pathophysiologic mechanisms underlying abnormalities in circadian BP, most importantly abnormalities in sympathetic nervous system activity, salt and volume balance, and activation of the renin-angiotensin system. Several of these factors can be modified by clinical interventions, eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 57 publications
1
28
0
6
Order By: Relevance
“…In recent years, a large number of preclinical and clinical studies have clearly identified the contribution of BPV to CV complications associated with hypertension [15,16]. Moreover, preliminary data from retrospective analysis of clinical trials suggest that BPV attenuation by antihypertensive agents is a factor in the prevention of major CV events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of preclinical and clinical studies have clearly identified the contribution of BPV to CV complications associated with hypertension [15,16]. Moreover, preliminary data from retrospective analysis of clinical trials suggest that BPV attenuation by antihypertensive agents is a factor in the prevention of major CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is one of leading risk factors of CV and cerebrovascular disease. 16.5% of all deaths worldwide can be attributed to high blood pressure (BP) [1][2][3]. When compared with others, patients with RA have increased CV morbidity and mortality that is primarily a result of premature atherosclerosis of coronary and cerebral arteries.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, measures as adoption of a more rigid treatment and the modification of medication administration horary could contribute with the improvement of these individuals' pressure profile and, consequently, change ND pattern 35 .…”
Section: Dm -Diabetes Mellitus; MI -Myocardium Infarction; Dlp -Dislimentioning
confidence: 99%
“…1,2 However, in as many as 25% to 35% of hypertensive patients, there is a moderate-to-marked loss of this decline in nocturnal BP, a phenomenon that has been associated with excessive cardiac, 3 renal, 4 and cerebrovascular 5 target organ damage. In addition, patients with hypertension who exhibit a nocturnal BP increase compared with daytime BP (so-called "risers") have the worst prognosis for future stroke and cardiac events.…”
mentioning
confidence: 99%